TRUST DAN RESPONS PSIKOLOGIS TERHADAP ARTIFICIAL INTELLIGENCE DALAM PEMBELAJARAN DIGITAL - Inka Sukma Melati; Amanda Pasca Rini; Salsabila R.K Syaharani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The development of Artificial Intelligence (AI) in digital learning has raised attention to aspects of trust and students' psychological responses. This study aims to systematically examine the relationship between trust and psychological responses to the use of AI in higher education using the Systematic Literature Review (SLR) method. A total of seven relevant articles were analyzed from systematic review, quantitative-qualitative, and experimental studies. The results show that trust plays an important role in increasing the frequency of AI use, learning motivation, student engagement, and perceptions of technology usefulness. High levels of trust are also associated with reduced technology anxiety and more positive attitudes toward AI, while low trust is related to resistance to use. Additionally, perceived benefits become the main predictor of AI usage intention, while trust serves as a supporting factor that strengthens technology acceptance. From a pedagogical perspective, AI does not replace the role of educators, but expands learning communication if designed in alignment with educational values and ethics. These findings emphasize the importance of strengthening trust, developing critical thinking, and reflective mechanisms so that AI integration in learning becomes more effective and meaningful. ABSTRAK Perkembangan Artificial Intelligence (AI) dalam pembelajaran digital memunculkan perhatian pada aspek kepercayaan (trust) dan respons psikologis mahasiswa. Penelitian ini bertujuan mengkaji secara sistematis hubungan trust dan respons psikologis terhadap penggunaan AI dalam pendidikan tinggi menggunakan metode Systematic Literature Review (SLR). Sebanyak tujuh artikel relevan dianalisis dari penelitian kajian sistematis, kuantitatif-kualitatif, dan eksperimen. Hasil menunjukkan bahwa trust berperan penting dalam meningkatkan frekuensi penggunaan AI, motivasi belajar, keterlibatan mahasiswa, serta persepsi kegunaan teknologi. Tingkat kepercayaan yang tinggi juga berkaitan dengan penurunan kecemasan teknologi dan sikap yang lebih positif terhadap AI, sedangkan rendahnya kepercayaan berhubungan dengan resistensi penggunaan. Selain itu, manfaat yang dirasakan menjadi prediktor utama niat penggunaan AI, sementara trust berfungsi sebagai faktor pendukung yang memperkuat penerimaan teknologi. Dari perspektif pedagogis, AI tidak menggantikan peran pendidik, tetapi memperluas komunikasi pembelajaran apabila dirancang selaras dengan nilai pendidikan dan etika. Temuan ini menegaskan pentingnya penguatan kepercayaan, pengembangan berpikir kritis, dan mekanisme reflektif agar integrasi AI dalam pembelajaran lebih efektif dan bermakna.